The United Nations and its Conflict Resolution Role - Ozev, Muharrem Hilmi; Erdogan, Aydin (Istanbul University Press, 2020)
While the United Nations was a concept describing the Allied forces combating the Axis powers during and immediately after World War II, it evolved into a more encompassing or universal concept over time as the traumas of war healed. In the 1990s, internal conflicts and terrorism increased, hence UN missions took on an anti-terror role. Technological and structural changes and the phase of globalization have made UN-centered global governance more important. Now, there is more active global public opinion, and it has turned its attention towards the UN. Today, it is almost impossible for the UN to provide the expected services using the methods, tools, and practices from the Cold War era. This situation is eroding the legitimacy of the UN and so the UN has become ineffective in solving global crises. Today, combating terrorism seems to gradually be losing its functionality in protecting the interests of the great powers. The shift in the balance of power in favor of rising powers, like China and India, has become the main threat to the status quo. Due to the shift in the power configuration within the P5 countries and the emergence of new forces not represented in P5, the UN may well become a stage for conflicting interests soon. The material basis for Chinese-US rivalry has already formed and when they produce intellectual and functional instruments, the struggle will inevitably focus on this rivalry. Therefore, in the near future, great powers will try to instrumentalize the UN and keep it in the spotlight as long as they consider it as functional in their struggles. Otherwise, the UN will gradually become an ineffective institution and it may even disappear altogether. Against this background, this collection represents the ideas of a group of conflict resolution experts from Turkey striving to explore the nature of the recent global political and sociological structuring and its possible consequences on the functions and the future of the UN. The collection contains articles that present general analyses pertaining to interesting country specific case studies and theoretical and practical issues. It also illuminates the positive and negative features of the UN conflict resolution attempts.